Pembuatan Perpustakaan Daring dengan Content Management System (CMS) untuk Perpustakaan Ramah Baca Samarinda - Kamila, Vina Zahrotun (ReTII, 2022)
Perpustakaan Mandiri Ramah Baca Samarinda Ulu is one of the libraries that is managed by individuals with the aim of increasing public interest in reading, especially for mothers and children. This library does not charge rent/borrow fees. So far, lending and borrowing procedures are managed manually and carried out through the Telegram messaging application. Library managers feel overwhelmed with current business processes. Especially during the pandemic, borrowing activities are carried out by courier. This condition ultimately makes Reading Friendly libraries need solutions to make book management and lending more practical and efficient. CMS (Content Management System) is a practical and fast way to build a website or web-based information system. With CMS, we can create the online libraries required by the Reading Friendly Libraries effectively and efficiently. With the implementation of the online library, it is hoped that the Perpustakaan Mandiri Ramah Baca Samarinda Ulu can improve efficiency and effectiveness in its business processes and reduce the complexity of managing manual book lending.